Fancies explained: Converting symbolic capital into NFTs - Serada, Alesha (Eludamos: Journal for Computer Game Culture, 2023)
The concept of symbolic capital, introduced by Pierre Bourdieu (1986), has been applied to explain the circulation of value between game communities and the industry. The bottom-up approach can be found in the studies of so-called “gaming capital” accumulated by gamers (Consalvo, 2009), while the top-down approach focuses on the agents who hold the most power in the gaming industry (Nichols, 2013). These perspectives may require reconfiguration today: since the end of the 2010s, traditional power relations have been contested by ‘decentralized’ gaming that uses blockchain technologies and non-fungible tokens (NFTs). Their early adopters suggest that NFTs may disrupt traditional circulation of value to the benefit of players as opposed to major corporations. Many gamers, however, vehemently oppose NFTs in games. By combining these top-down and the bottom-up approaches, this article explains that the specific symbolic gaming capital remains systematically underappreciated in blockchain gaming, which operates along different vectors of power. To support my argument, I turn to the longest-running blockchain-based game CryptoKitties (Axiom Zen, 2017), and analyze the elements of the role-playing genre that appeared in the game during the collective process of continuous development. In the first case, these elements (‘fancies’) were added by the developers of the game, and in the second case, an RPG-like extension emerged as one of its fan spin-offs (KotoWars). I conclude that symbolic capital is community-specific in the case of blockchain gaming. It is only available to those who already possess considerable symbolic, and, much more importantly, financial capital within the crypto community.